2008
DOI: 10.1159/000178026
|View full text |Cite
|
Sign up to set email alerts
|

Employing RMR Technology in a 90-Day Weight Control Program

Abstract: Objective: The purpose of this study was to evaluate the efficacy of a weight management program using indirect calorimetry to set energy goals. Methods: 54 overweight, active duty adult employees of the US Air Force (age 18–46 years, BMI 25.2–35.6 kg/m2) participated in this quasi-experimental control design study. All participants were enrolled in a four-session US Air Force ‘Sensible Weigh’ group weight control program. Treatment participants received a personalized nutrition energy goal message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…UE experienced a steady decline throughout the study. These results are similar to the previous studies employing higher levels of calorie intake plans (22,23). Beasley et al (22) demonstrated a reduction in appetite following a 6-week period of consuming a 25% protein, 2100 kcal ⁄ day.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…UE experienced a steady decline throughout the study. These results are similar to the previous studies employing higher levels of calorie intake plans (22,23). Beasley et al (22) demonstrated a reduction in appetite following a 6-week period of consuming a 25% protein, 2100 kcal ⁄ day.…”
Section: Discussionsupporting
confidence: 89%
“…1200-1600 kcal ⁄ day) (4-9,15). In addition, MD participants experienced similar weight loss ()5.7 ± 7.1 kg) to the previous studies employing metabolic-based diet plans (21,23). Weight loss between groups was not significantly different.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These small changes in nutrition (energy intake) in addition to physical activity behaviors can prevent weight gain (35). Thus, an individually measured REE provides an additional tool to aid in the weight management strategy, as shown earlier in overweight US Air Force personnel (36). This aspect of an objective measurement of REE-based diet and nutrition counseling, may provide an additional tool in the treatment and management of overweight and obese adolescents, and needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…. Energy/caloric metabolism activity indicated by RMR and PPEE was measured by breath oxygen volume (VO 2 ; ml/min) using hand-held indirect calorimeter (MedGem ® test kit, Microlife ® , Golden, CO) [40] in a separate independent study from Study 1. Test procedures are shown in Figure 2B.…”
Section: ) Resting Metabolic Rate (Rmr) and Ppee Measurement (Study 2)mentioning
confidence: 99%